Implementasi Kriptografi dengan Caesar Cipher pada Fitur Pesan di WhatsApp untuk Keamanan - Ratih Adinda Destari (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Rapid technological developments have penetrated various aspects of human life, including data and information security. Amidst the threat of data leaks and misuse, information protection has become crucial. One solution to maintain data confidentiality is to implement cryptography technology. Cryptography is the study of techniques to secure messages so they cannot be read by unauthorized parties. This process is carried out by encoding the original message (plain text) into an unreadable form (cipher text), which can only be understood by those who possess the key to decrypt it. This study used the Caesar Cipher algorithm, a form of classical cryptography. This algorithm uses a substitution method, where each letter in the message is shifted by a certain amount based on a predetermined key. Caesar Cipher is a symmetric algorithm, meaning the key used for encryption is also used for decryption. The security of this algorithm lies in the secrecy of the key, which is known only to the sender and recipient of the message. This method is relatively simple, but still relevant for securing data with low to medium sensitivity levels. This study used WhatsApp messages as the object to be encrypted using the Caesar Cipher algorithm. The results show that encrypted messages become unintelligible without prior decryption. This demonstrates that the Caesar Cipher can protect messages from unauthorized parties. Therefore, implementing this algorithm can be an initial solution for maintaining data confidentiality in digital communications, especially on platforms vulnerable to eavesdropping or unauthorized access. Its primary benefit is maintaining message integrity and confidentiality to prevent misuse.